Oronasal fistula repair with Combined Endoscopic & Transoral Approach (3 layer): Case report & Review of Literature - Aggarwal, Ankita; Yadav, Vishav; Bhagat, Sanjeev; Sharma, Dinesh Kumar; Goel, Khushboo (GMC Patiala Journal of Research and Medical Education, 2022)
A 24 year old female patient presented with symptoms of nasal regurgitation of liquid feeds lasting since 2 years. On examination patient was found to have oronasal fistula with necrotic exposed maxillary bone (palatal surface). In view of failure of response to conservative management, patient was operated with Combined Transoral- Endoscopic approach (3 layer repair). Patient was under follow up for 1 year and was asymptomatic till last follow up. We shall review the literature of oronasal fistula with respect to etiopathogenesis and management options.